PENERAPAN STANDART PENCATATAN LAPORAN KEUANGAN SAK- EMKM PADA TOKO DNR BAGS & BOUTIQUE - Dianafitri, Siska (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose of this study is to find out how the financial statements of MSMEs DNR Bags & Boutique are in accordance with SAK-EMKM standards or not, and analyze how the financial statements of MSMEs DNR Bags & Boutique are currently applied. The focus of this study uses a Qualitative approach. In this study, observation, interviews, and documentation are used as data collection procedures and analyzed using qualitative techniques. The results showed that (1) DNR Bags & Boutique stores have not implemented financial statement recording standards in accordance with SAK-EMKM (2) Financial statements DNR Bags & Boutique stores only record such as cash in, cash out, incoming goods, and outgoing goods (3) Unavailability of human resources who master or know the process of preparing financial statements in accordance with SAK-EMKM standards.